INVESTMENT PRIORITIES IN THE AGRICULTURAL SCIENTIFIC RESEARCH IN IRAQ USING POLICY ANALYSIS MATRIX APPROACH CEREALS CROPS (RICE AMBER AL BARAKA BUHOOTH2, CORN SYNTHETIIC GENOTYPE FAJER 1, AND WHEAT BUHOOTH 158) STUDY CASE - & et al., Lateef (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The aim of this study is to focus on the investment priorities in the agricultural scientific research in Iraq for three cereals crops (Rice Amber Al Baraka Buhooth2, Corn Synthetic genotype Fajer1, and wheat Buhooth158) for the year (2012) respectively by using analysis method named police Analysis Matrix. This method is considered being a way of knowing the impact of investment in the agricultural scientific research, and it is done by calculating Profitability coefficient, Domestic Resource Cost coefficient, Producer Subsidy Ratio coefficient, and Private Cost coefficient Ratio for the cereals crops mentioned above. The research found a set of results, the most important result showed that .The investment was profitable for domestic producer for the wheat Buhooth158 for the year 2012 based on the values of profitability coefficient which was about 2.93 and private cost coefficient ratio which was about 0.44 , producer subsidy ratio coefficient which was 45.36% and private profits which were 450140 respectively . The investment was profitable for domestic producer for the variety Amber Al Baraka Buhooth2 for the year 2012 based on the values of profitability coefficient which was about 2.57, private cost coefficient ratio which was about 0.31 , producer subsidy ratio coefficient which was 60.87% and private profits which were 857360 respectively. The investment was profitable for domestic producer for the variety Synthetic genotype Fajer1 for the year 2012 based on the values of profitability coefficient which was about 1.78 and private cost coefficient ratio which was about 0.17 and producer subsidy ratio coefficient which was 49.95% and private profits which were 1458574 respectively Finally, it is highly recommended that support should be increased for variety that the country has greater comparative advantage in order to improve the utilization of available resources and reduce wasted resources. Moreover, similar studies should be done in the future by other researchers for the major cereal crops at the country level in order to do comparison between them to set an investment mechanism which help both the researcher, local producer and agricultural investor in directing its resources.